A novel strategy for evaluation of natural products acting on the myeloperoxidase/hypochlorous acid system by combining high‐performance liquid chromatography‐photodiode array detection‐chemiluminescence and ultrafiltration‐mass spectrometry techniques. Issue 22 (2nd November 2018) - Wang, Ying; Hong, Fang; Li, Dapeng; Qi, Jin; Liu, Xuming
Abstract: Myeloperoxidase and its product hypochlorous acid are endogenous substances that are involved in the pathogenesis of many inflammatory diseases. In the present study, a novel evaluation strategy has been developed to screen for myeloperoxidase inhibitors and hypochlorous acid scavengers in natural products. The evaluation strategy uses two methods: a multi‐hyphenated high‐performance liquid chromatography‐photodiode array detection‐chemiluminescence online method, and an ultrafiltration‐high‐performance liquid chromatography‐mass spectrometry method. Both were used for screening hypochlorous acid scavengers and myeloperoxidase inhibitors. After optimization of operating conditions, including pH of mobile phase and concentrations of myeloperoxidase, hypochlorous acid and luminol, the evaluation strategy was applied to Gardenia jasminoides Ellis (Rubiaceae) extract. Gardenia jasminoides Ellis (Rubiaceae) extract was found to both scavenge hypochlorous acid and inhibit myeloperoxidase. These different bioactivities originate from iridoid glycosides and quinic acid derivatives (25 hypochlorous acid scavengers) and crocetin derivatives (4 myeloperoxidase inhibitors). In a mouse model of acute lung injury, pulmonary histopathology showed that different constituents of Gardenia jasminoides Ellis (Rubiaceae) extract could also attenuate lung injury. Although the screening strategy has two arms, it is still simple, rapid, and effective. The strategy can also potentially be used to discriminate different activities of different constituents contained in the same natural product.